Elementary School Students' Understanding and Attitudes towards Air Pollution Around the School Environment - Rahmawati, Rahmawati; Mustoip, Sofyan; Auliyani, Fitri (LJPI UI Bunga Bangsa Cirebon, 2024)
This research aims to understand how elementary school students view and behave towards air pollution around the school environment. Using a qualitative approach, this research involved in-depth interviews with students from several elementary schools in urban areas that are exposed to significant levels of air pollution. The data obtained was analyzed thematically to identify students' perceptions regarding the impact of air pollution on their health and the actions they consider necessary to reduce pollution. The research results show that most students have a basic understanding of air pollution, but their knowledge about its impact on health is still limited. Students' attitudes tend to be passive, although they show a desire to be involved in environmental conservation efforts through simple activities at school. This research provides important insights for the development of more effective educational programs to increase students' awareness of the importance of maintaining the air quality around them.